Strength development and hydration products of alkali-activated Pisha sandstone geopolymer cement - Dong, Jingliang; Li, Lianghua; Shi, Zhenhua; Ding, Yang; Chen, Xiaolei; Zong, Yingliang (Frontiers in Materials, 2023)
Pisha Sandstone (PS) is a unique geological structure in the Yellow River basin in China, which is a general term for a rock interlayer composed of sandstone, sand shale and muddy sandstone.And the collapsibility of PS results in a high erosion rate as well as poor vegetation due to its low diagenetic potential and weak structural strength. This study showed that PS can be converted to geopolymer cement by mixing with suitable alkali activator. In order to control soil erosion and conserve the soil and water in this area, PS was converted to a geopolymer cement for construction.Slag was used as mineral additive to improve the performance of alkali active PS geopolymer cement in this paper. The influence of slag replacement level, NaOH dosages and curing age on the compressive strength of alkali-activated PS were studied. Scanning electron microscopy (SEM)/energy dispersive X-ray (EDS), Thermoravimetric analyses (TG/DTG) and X-ray diffraction (XRD) were used to analyze the hydration products and microstructure of alkali-activated PS. The results showed when the samples with 40 wt.% slag, 1.5 wt.%NaOH and 4.0wt.% Na2SiO3, the compressive strength samples can reach 82.0MPa at 90 days. Compared with the samples with activator and without activator, the compressive strength increased by 6664% and 9011%. And the hydration products are C-S-H gel, geopolymer gel and calcium carbonate crystals. When with 10 wt.% slag as mineral additive and with 1.5 wt.% NaOH, 4 wt.% Na2SiO3 as activator, the carbonation ratio of C-S-H gel is 49.3%.